Barriers to Implementing a Reporting and Learning Patient Safety System: Pediatric Chiropractic Perspective. (April 2016) - Pohlman, Katherine A.; Carroll, Linda; Hartling, Lisa; Tsuyuki, Ross T.; Vohra, Sunita
A reporting and learning system is a method of monitoring the occurrence of incidents that affect patient safety. This cross-sectional survey asked pediatric chiropractors about factors that may limit their participation in such a system. The list of potential barriers for participation was developed using a systematic approach. All members of the 2 pediatric councils associated with US national chiropractic organizations were invited to complete the survey (N = 400). The cross-sectional survey was created using an online survey tool (REDCap) and sent directly to member emails addressed by the respective executive committees. Of the 400 potential respondents, 81 responded (20.3%). The most common limitations to participating were identified as time pressure (96%) and patient concerns (81%). Reporting and learning systems have been utilized to increase safety awareness in many high-risk industries. To be successful, future patient safety studies with pediatric chiropractors need to ensure these barriers are understood and addressed.